Spatiotemporal and Functional Characterisation of the Plasmodium falciparum cGMP-Dependent Protein Kinase - Hopp, Christine S. (Public Library of Science, 2012)
Signalling by 3′–5′-cyclic guanosine monophosphate (cGMP) exists in virtually all eukaryotes. In the apicomplexan parasite Plasmodium, the cGMP-dependent protein kinase (PKG) has previously been reported to play a critical role in four key stages of the life cycle. The Plasmodium falciparum isoform (PfPKG) is essential for the initiation of gametogenesis and for blood stage schizont rupture and work on the orthologue from the rodent malaria parasite P. berghei (PbPKG) has shown additional roles in ookinete differentiation and motility as well as liver stage schizont development. In the present study, PfPKG expression and subcellular location in asexual blood stages was investigated using transgenic epitope-tagged PfPKG-expressing P. falciparum parasites. In Western blotting experiments and immunofluorescence analysis (IFA), maximal PfPKG expression was detected at the late schizont stage. While IFA suggested a cytosolic location, a degree of overlap with markers of the endoplasmic reticulum (ER) was found and subcellular fractionation showed some association with the peripheral membrane fraction. This broad localisation is consistent with the notion that PfPKG, as with the mammalian orthologue, has numerous cellular substrates. This idea is further supported by the global protein phosphorylation pattern of schizonts which was substantially changed following PfPKG inhibition, suggesting a complex role for PfPKG during schizogony.